Kinetic changes during a six-week minimal footwear and gait-retraining intervention in runners - Warne, J. P.; Smyth, B. P.; O`C Fagan, J.; Hone, M. E.; Richter, C.; Nevill, A. M.; Moran, K. A.; Warrington, G. D. (Journal of Sports Sciences, 2017)
An evaluation of a six-week Combined minimal footwear transition and gait-retraining combination vs. gait retraining only on impact characteristics and leg stiffness. Twenty-four trained male runners were randomly assigned to either (1) Minimalist footwear transition Combined with gait-retraining over a six-week period ("Combined" group; n = 12) examined in both footwear, or (2) a gait-retraining group only with no minimalist footwear exposure ("Control"; n = 12). Participants were assessed for loading rate, impact peak, vertical, knee and ankle stiffness, and foot-strike using 3D and kinetic analysis. Loading rate was significantly higher in the Combined group in minimal shoes in pre-tests compared to a Control (P = 0.001), reduced significantly in the Combined group over time (P = 0.001), and was not different to the Control group in post-tests (P = 0.16). The impact peak (P = 0.056) and ankle stiffness reduced in both groups (P = 0.006). Loading rate and vertical stiffness was higher in minimalist footwear than conventional running shoes both pre (P = 0.001) and post (P = 0.046) the intervention. There has a higher tendency to non-rearfoot strike in both interventions, but more acute changes in the minimalist footwear. A Combined intervention can potentially reduce impact variables. However, higher loading rate initially in minimalist footwear may increase the risk of injury in this condition.